Distribution Record of Leptophryne borbonica (Tschudi, 1838) (Anura: Bufonidae) from Malang, East Java: Description, Microhabitat, and Possible Threats - Muhamad Prayogi Erfanda; Luhur Septiadi; Sandra Rafika Devi; Berry Fakhry Hanifa (Universitas Gadjah Mada, 2019)
Bromo Tengger Semeru National Park (TNBTS) which partly located in Malang, East Java, Indonesia holds various kinds of niches that can support the existence of undiscovered amphibian species. We examine a new distribution of the Leptophryne borbonica, Hourglass-toad from an area located on the slopes of the Southwest of Tengger Mountain as well as its ecological implications related to the possibility of habitat threats. The exploration was carried out on January 1st and March 1st, 2019, with the description of morphology data and collecting abiotic parameters such as temperature, humidity, altitude, and habitat preference. The distribution of the species was marked. Any important notable records of the habitat threats are documented. The results showed that the amphibians found were Leptophryne borbonica, and set as a new record on Malang, East Java. We suggested that the isolated distribution is very susceptible to ecological disturbances, future ecotourism development, and habitat destruction that prone to local extinction. Further research and conservation efforts need to be carried out for the sustainability of this species in the observation site.